2014
DOI: 10.5194/se-5-183-2014
|View full text |Cite
|
Sign up to set email alerts
|

The ring-shaped thermal field of Stefanos crater, Nisyros Island: a conceptual model

Abstract: Abstract. Fumarole fields related to hydrothermal processes release the heat of the underground through permeable pathways. Thermal changes, therefore, are likely to depend also on the size and permeability variation of these pathways. There may be different explanations for the observed permeability changes, such as fault control, lithology, weathering/alteration, heterogeneous sediment accumulation/erosion and physical changes of the fluids (e.g., temperature and viscosity). A common difficulty, however, in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…4a). As mentioned in the BIntroduction,p athways of the ascending fluids including CO 2 are controlled by topography, lithology, and/or volcano-tectonic structures (Schöpa et al 2011;Peltier et al 2012;Pantaleo and Walter 2014;Hutchison et al 2015). Here, we evaluate possibilities of these factors.…”
Section: Pathway Of Diffuse Comentioning
confidence: 97%
See 3 more Smart Citations
“…4a). As mentioned in the BIntroduction,p athways of the ascending fluids including CO 2 are controlled by topography, lithology, and/or volcano-tectonic structures (Schöpa et al 2011;Peltier et al 2012;Pantaleo and Walter 2014;Hutchison et al 2015). Here, we evaluate possibilities of these factors.…”
Section: Pathway Of Diffuse Comentioning
confidence: 97%
“…Pantaleo and Walter (2014) suggested that permeability contrasts generated by depositional processes may control an evolution of fumarole fields. A similar idea is also presented in Peltier et al (2012).…”
Section: Pathway Of Diffuse Comentioning
confidence: 98%
See 2 more Smart Citations
“…In fact, in the last 30 years, CO 2 spatial distribution has been used worldwide to identify hidden tectonic structures, since faults/fractures act as preferential pathways (high permeability zones) for the escape of gases from the deep crust or mantle to the surface (Giammanco et al, 1999(Giammanco et al, , 2006Baubron et al, 2002;Hutchison et al, 2015;Liuzzo et al, 2015). Based on the release of soil gases in confined areas, Chiodini et al (2001) named the anomalous CO 2 degassing areas, where hydrothermal/volcanic CO 2 is released, as diffuse degassing structures (DDS), whose shape depends on morphological, geological, and structural factors, such as the topography, existence of lithological heterogeneities, and presence of faults/fractures (Schöpa et al, 2011;Peltier et al, 2012;Pantaleo and Walter, 2014).…”
mentioning
confidence: 99%